Evidence‐Based Teaching in Higher Education: Application to Counselor Education. (1st December 2014) - Malott, Krista M.; Hall, K. Hridaya; Sheely‐Moore, Angela; Krell, Megan M.; Cardaciotto, LeeAnn
Abstract : The authors examined best practices in university‐level teaching, as premised on the evidence‐based teaching (EBT) literature found in fields external to counselor education. Findings were reported in relation to 3 areas: developing an effective learning environment, structuring intentional learning experiences, and assessing teaching effectiveness. Implications regarding the training of doctoral‐level counselor educators using EBT practices are discussed.